2023
DOI: 10.1093/heapro/daad098
|View full text |Cite|
|
Sign up to set email alerts
|

Creating healthy food environments in recreation and sport settings using choice architecture: a scoping review

Rachel Prowse,
Natasha Lawlor,
Rachael Powell
et al.

Abstract: Recreation and sport settings (RSS) are ideal for health promotion, however, they often promote unhealthy eating. Choice architecture, a strategy to nudge consumers towards healthier options, has not been comprehensively reviewed in RSS and indicators for setting-based multi-level, multi-component healthy eating interventions in RSS are lacking. This scoping review aimed to generate healthy food environment indicators for RSS by reviewing peer-reviewed and grey literature evidence mapped onto an adapted choice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…Four guiding principles (availability, pricing and placement, promotion, and provider commitment) have been recommended for successful implementation of healthy food environments in recreation and sports settings [12]. As demonstrated through the results of this study, these can be adapted and applied in the context of major competitions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Four guiding principles (availability, pricing and placement, promotion, and provider commitment) have been recommended for successful implementation of healthy food environments in recreation and sports settings [12]. As demonstrated through the results of this study, these can be adapted and applied in the context of major competitions.…”
Section: Discussionmentioning
confidence: 98%
“…The more commonly implemented strategies that promote behaviour change, such as nutrition labelling of menu items, educational information, and changes to serving plates and cutlery, have inconclusive outcomes [10]. Research in recreation and sports settings has suggested that multi-level setting-based approaches may be more impactful than a singular intervention [12]. Menu labelling alone has been shown to have a moderate impact on altering the intake of specific nutrients and dietary components of consumers [13], yet the impact on athletes' diets is unknown.…”
Section: Introductionmentioning
confidence: 99%